Differential expression of circulating micro-RNAs in patients with active tuberculosis and infected with latent tuberculosis - Jose Yareta; Marco Galarza; Silvia Capristano; Oscar Pellón; César Sánchez; Jorge Ballon; Heinner Guio (Revista Peruana de Medicina Experimental y Salud Pública, 2020)
Objectives: To analyze the differential expression of miR-21, miR-29a, miR-99b and miR-155 in serum samples from patients with latent tuberculosis (TB) and active TB compared to healthy controls. Materials and Methods: We used 28 serum samples (9 with active TB, 10 with latent TB and 9 healthy controls) for the analysis of gene expression by RT-qPCR with Primers and TaqMan probes. The differential expression was calculated by the Livak method using a normalizing gene (RNU-48). Results: Overexpression of miR-155 was found in people with latent tuberculosis, compared to healthy controls (0.63 vs. 0.01; p value = 0.032). Conclusion: The miR-155 could be considered a biomarker to differentiate latent TB from active disease. Studies with larger sample sizes are required to corroborate the findings.